Archeoakustyka. Pomiędzy słuchaniem przeszłości a przepisywaniem historii - Misiak, Tomasz (Folia Praehistorica Posnaniensia, 2019)
The main problem presented in the article is archeoacoustics understood as a modern subdiscipline of archeology. The aim of the research was to outline the theoretical map of ideological references used by this young, still developing field. In order to understand the complex interdisciplinary nature of the archeoacoustic approach, ideological concepts were indicated and described, which, starting from various research assumptions, reflected on the role and methods of the impact of the sound in culture.